2021
DOI: 10.3389/fmed.2020.628289
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines in Diabetic Kidney Disease: Pathophysiologic and Therapeutic Implications

Abstract: Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease and a main contributing factor for cardiovascular morbidity and mortality in patients with diabetes mellitus. Strategies employed to delay the progression of this pathology focus on the control of traditional risk factors, such as hyperglycemia, and elevated blood pressure. Although the intimate mechanisms involved in the onset and progression of DKD remain incompletely understood, inflammation is currently recognized as one of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 118 publications
2
34
0
Order By: Relevance
“…Some studies have shown that inflammation markers and oxidative stress are elevated in patients with chronic kidney disease and the present study shows an association between inflammatory markers and reduced renal function in cases of HEmerg [11,38]. Similarly, inflammatory cytokines are predictors of the initiation and progression of diabetic kidney disease, regulating the immune response and exerting important actions as effectors of lesions, including the development of nephropathy [39]. In the present work, all the cytokines were higher in the HC group compared to control groups.…”
Section: Discussionsupporting
confidence: 66%
“…Some studies have shown that inflammation markers and oxidative stress are elevated in patients with chronic kidney disease and the present study shows an association between inflammatory markers and reduced renal function in cases of HEmerg [11,38]. Similarly, inflammatory cytokines are predictors of the initiation and progression of diabetic kidney disease, regulating the immune response and exerting important actions as effectors of lesions, including the development of nephropathy [39]. In the present work, all the cytokines were higher in the HC group compared to control groups.…”
Section: Discussionsupporting
confidence: 66%
“…TNFα concentration was enhanced even in tear fluids, which correlated well with the severity of diabetic retinopathy [31]. Increased TNFα levels have been related to the development of diabetic nephropathy involving reactive oxygen species accumulation and related cytotoxicity in kidney cells [32][33][34]), while TNFα inhibition ameliorated the glomerular and tubular injury in diabetic kidney [35]. TNFα is directly involved in the destruction of β-cells in isolated islets [36] and plays a key role in the onset of diabetes in mice through the regulation of dendritic cell maturation and activation of islet-specific pancreatic T-cells [37].…”
Section: Introductionmentioning
confidence: 94%
“…There is growing evidence that kidney inflammation plays a vital role in the occurrence and development of DKD [ 3 ]. Inflammation and oxidative stress are strongly correlated with the risk of developing DKD [ 4 6 ]. Immune cell infiltration (mainly macrophages) of renal tissue is increased in both animal models and patients with DKD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%